Auditing gender in agricultural R&D organizations: gender mainstreaming in the CGIAR - CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation (2009)
The CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation (PRGA Program) conducted valuable work on gender mainstreaming in NARS in Africa, Asia and Latin American during its second phase (2003–2007), and developed key gender models and typologies during its first phase (1997–2002). Meanwhile, various efforts have been made to introduce gender analysis into the wider CGIAR System throughout the life of the Program.